2016
DOI: 10.1021/acs.analchem.6b03553
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry and Ion Mobility Characterization of Bioactive Peptide–Synthetic Polymer Conjugates

Abstract: The bioconjugate BMP2-(PEO-HA), composed of a dendron with two monodisperse poly(ethylene oxide) (PEO) branches terminated by a hydroxyapatite binding peptide (HA), and a focal point substituted with a bone growth stimulating peptide (BMP2), has been comprehensively characterized by mass spectrometry (MS) methods, encompassing matrix-assisted laser desorption ionization (MALDI), electrospray ionization (ESI), tandem mass spectrometry (MS), and ion mobility mass spectrometry (IM-MS). MS experiments using differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Remarkably, the IM‐MS experiments showed the existence of random coil and helical conformers in both the peptides and the bioconjugates. Moreover, the IM‐MS data also suggested that the helical structure was stabilized by PEG attachment at the C‐terminus …”
Section: Characterization Of Bioresorbable Polymers By Msmentioning
confidence: 97%
See 1 more Smart Citation
“…Remarkably, the IM‐MS experiments showed the existence of random coil and helical conformers in both the peptides and the bioconjugates. Moreover, the IM‐MS data also suggested that the helical structure was stabilized by PEG attachment at the C‐terminus …”
Section: Characterization Of Bioresorbable Polymers By Msmentioning
confidence: 97%
“…Both MALDI and ESI MS, in some cases with the support of MS/MS and/or IM‐MS, have been used in the characterization of polymer conjugates, to confirm the effective functionalization and the success of the synthetic approch . The transesterification reaction of PHAs has been used as a strategic and simple tool for the synthesis of delivery systems for selected bioactive compounds, holding carboxyl or hydroxyl functionalities.…”
Section: Characterization Of Bioresorbable Polymers By Msmentioning
confidence: 99%
“…In addition to metal adduction, protonation was also envisaged in particular cases where synthetic polymers were conjugated with moieties of high proton affinity, in particular peptides . For example, Wesdemiotis and co‐workers reported that the helical structure of alanine‐rich peptides is further stabilized upon conjugation with PEG via their C‐terminus .…”
Section: Investigation Of Gas‐phase Ion Structuresmentioning
confidence: 99%
“…1,2 When coupled with molecular simulations and modeling, IM-MS can provide conclusive evidence about the spatial arrangement and conformation of proteins, [3][4][5] glycans, 6 and lipids, 7 as well as the topology and architecture of synthetic polymers [8][9][10][11][12][13] and bioconjugates. [13][14][15] Over the past years, significant progress has been made in the development of simple, one-step, quantitative methods for the conversion of polyfunctional monomers with well-defined geometries into supramolecular constructs with useful physicochemical properties. [16][17][18][19][20] Terpyridine (tpy)-based coordinative chemistry with various metal 2+ ions, in particular, has enabled the synthesis of a vast array of macrocyclic and multicyclic compounds carrying the <tpy-Metal 2+ -tpy> connectivity and having precise metal/ligand stoichiometries and specific, predesigned 3D geometries, depending on the molecular structure of the tpy ligand.…”
Section: Introductionmentioning
confidence: 99%